Manajemen Stres: Pikiran Sehat, Komunikasi Sehat dengan Penerapan Mindfulness - Marchelina Febe Sumbaga (Devotion : Jurnal Pengabdian Psikologi, 2022)
Employee performance is often associated with work effectiveness, but if you look a step back, these two things stem from one thing, namely work stress. When employees experience stress at work, their performance will decrease. Likewise, their effectiveness at work will indirectly be affected and will ultimately have an impact on the company. There are various things that can make an employee experience stress at work, both from internal and external influences. For this reason, stress at work must be immediately followed up as a form of prevention against decreasing employee effectiveness at work. One of them is to apply stress management that can be done with the mindfulness method. When this method is applied, it is believed that it will reduce stress on employees not only in the work environment, but also in daily life. This method can make one's life more meaningful and happier so that it has an impact on one's mindset when dealing with a problem so that the welfare and mental health of employees will be able to improve. This improvement in conditions will provide many positive benefits for the company, and the individual itself of course.